A green technology for the synthesis of cellulose succinate for efficient adsorption of Cd(ii) and Pb(ii) ions. Issue 32 (14th March 2016) - Qin, Xingzhen; Zhou, Jierong; Huang, Aimin; Guan, Jialin; Zhang, Qinglong; Huang, Zuqiang; Hu, Huayu; Zhang, Yanjuan; Yang, Mei; Wu, Juan; Qin, Yuben; Feng, Zhenfei
Abstract : Cellulose succinate, directly prepared by a simple and green mechanical activation-assisted solid-phase synthesis method in a stirring ball mill, was used as environmental-friendly adsorbent for efficient adsorption of heavy metals. Abstract : Cellulose succinate, which was used for efficient adsorption of heavy metals, was directly prepared by mechanical activation (MA)-assisted solid-phase synthesis in a stirring ball mill with bagasse pulp and succinic acid as materials without the use of organic co-reagents and solvents. FTIR, XRD, SEM, and specific surface area analysis were used to characterize the structural characteristics of cellulose succinate. Furthermore, the effects of different degrees of esterification of modified cellulose on the adsorption of Cd 2+ and Pb 2+ were investigated. A surface charge characteristic was used to prove the effect of pH on the adsorption ability of cellulose succinate. It was found that the adsorption kinetics of Cd 2+ and Pb 2+ onto cellulose succinate fitted well with the pseudo-second-order model. The adsorption of Cd 2+ and Pb 2+ onto cellulose succinate was well described by the monolayer adsorption of the Langmuir isotherm model rather than the multilayer adsorption of the Freundlich isotherm model. The E values for the adsorption of Cd 2+ and Pb 2+ by cellulose succinate calculated by the Dubinin–Radushkevich equation were all in the range of 8–16 kJ mol −1, suggesting that the adsorption process mainly proceeded by ion exchange. The MA-assisted solid-phase synthesis method can produce efficient and environmental-friendly adsorbents.